DIABETIC RETINOPATHY: AN INCLUSIVE REVIEW ON CURRENT TREATMENT AND MANAGEMENT APPROACHES - S L, Jyothi; Gupta N, Vishal (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Diabetic retinopathy (DR) is a complication which occurs due to diabetes mellitus leading to loss of vision and hindering the quality of patient life by damaging the layer of retina at the posterior segment of the eye. According to the survey around 285 million peoples are suffering from visual loss out of these 65% of people are more than 50 years old and 82% of blind patients are more than 50 years old. The diseases that occur in the posterior segment of the eye like, cytomegalovirus retinitis, posterior uveitis, age related macular degeneration and diabetic retinopathy needs a novel delivery system that can improve the concentration of drugs that reaches posterior segment of the eye. The development of new drug delivery system gained more importance in the field of research in which nanotechnology is the most considered approach. The nanotechnology-based systems such as nanoparticles, nanoliposomes, niosomes, nanomicelles, nanoemulsions, nanogels, cyclodextrins, dendrimers, and quantum dots are developed as a new formulation for drug delivery. The rationale behind the nanoparticle systems is its ability to formulate a sustained, controlled release dosage form, painless, safe, non-invasive system to overcome the major barriers in the treatment of DR. Based on the nanoparticles, some approaches are exploited for more effective conveyance of drug toward the posterior segment. Thus, these advanced delivery systems progress the therapeutic efficacy of the drug and patient's obedience and life quality. In this review, the new therapeutic treatments and their managements were discussed and methods of drug delivery to reach the posterior segment of eye.